Effects of Acute–Postacute Continuity on Community Discharge and 30‐Day Rehospitalization Following Inpatient Rehabilitation. (5th June 2017) - Graham, James E.; Prvu Bettger, Janet; Middleton, Addie; Spratt, Heidi; Sharma, Gulshan; Ottenbacher, Kenneth J.
Abstract : Objective: To examine the effects of facility‐level acute–postacute continuity on probability of community discharge and 30‐day rehospitalization following inpatient rehabilitation. Data Sources: We used national Medicare enrollment, claims, and assessment data to study 541, 097 patients discharged from 1, 156 inpatient rehabilitation facilities (IRFs) in 2010–2011. Study Design: We calculated facility‐level continuity as the percentages of an IRF's patients admitted from each contributing acute care hospital. Patients were categorized into three groups: low continuity (<26 percent from same hospital that discharged the patient), medium continuity (26–75 percent from same hospital), or high continuity (>75 percent from same hospital). The multivariable models included an interaction term to examine the potential moderating effects of facility type (freestanding facility vs. hospital‐based rehabilitation unit) on the relationships between facility‐level continuity and our two outcomes: community discharge and 30‐day rehospitalization. Principal Findings: Medicare beneficiaries in hospital‐based rehabilitation units were more likely to be referred from a high‐contributing hospital compared to those in freestanding facilities. However, the association between higher acute–postacute continuity and desirable outcomes is significantly better in freestanding rehabilitation facilities than in hospital‐based units. Conclusions: Improving continuity is a key premise of health care reform. We found that both observed referral patterns and continuity‐related benefits differed markedly by facility type. These findings provide a starting point for health systems establishing or strengthening acute–postacute relationships to improve patient outcomes in this new era of shared accountability and public quality reporting programs.